Optimization Of Regional Levy Revenue, In The City Of Surabaya, East Java Province - Marja Sinurat; Rosmery Elsye; Gusty Setyono; Salahudin Ansari; Khairatul Fatati (Jurnal Scientia, 2024)
Increasing regional income is one of the government's foundations for carrying out development and improving people's lives. The aim of this research is to describe and analyze the process of optimizing regional levy revenue in the City of Surabaya, describe and analyze the obstacles and weaknesses in optimizing regional levy revenue in the City of Surabaya, and describe and analyze efforts to optimize regional levy revenue in the City of Surabaya. The research method used is qualitative with data collection techniques through interviews, observation and documentation. This research uses Optimization theory (Adisasmita, 2011) with the dimensions of expanding the revenue base, strengthening the collection process, improving supervision, increasing administrative efficiency and reducing collection costs, and increasing revenue capacity through more targeted planning. The research results show that the process of optimizing regional levy revenue in the City of Surabaya has been carried out by the Surabaya City Government but has not been optimal so it has not been able to achieve the realization target. Obstacles and weaknesses in optimizing regional levy revenue in the city of Surabaya include studies that are not in line with targets, limited construction of objects due to the budget, as well as expanding the revenue base which is hampered by complex administration and low public awareness of paying. Efforts to optimize regional levy revenue for the City of Surabaya that have been made include increasing the budget for studying potential levies, adding new parking points, and developing a technology-based collection system. The researcher's suggestion in order to optimize regional levy revenue is that a comprehensive analysis of Surabaya City regional levies is needed so that the policy direction is clear and focused.